OR21-01 Pre-Operative Calcitonin Value as a Predictive Factor of Cancer Related Death in Sporadic Medullary Thyroid Carcinoma - Matrone, Antonio (J Endocr Soc, 2020)
Introduction: Medullary thyroid carcinoma (MTC) is a rare tumor, it originates from the C cells producing calcitonin (CT) and can occur as sporadic or associated to germline RET mutation. The initial treatment is represented by total thyroidectomy associated with central compartment lymph nodes dissection and possible extension to the laterocervical compartment. CT is the main marker of follow-up of MTC, conversely its pre-operative role as diagnostic and prognostic factor is still debated. The aim of the present study was to evaluate several predictive factors of cancer related death in a large series of sporadic MTCs. Patients and Methods: We evaluated 537 consecutive patients surgically treated for sporadic MTC, from 2000 to 2019, and followed at the Operative Unit of Endocrinology 1 of the University of Pisa. We evaluated epidemiological, clinical and pathological data and pre and post-operative CT values, and their correlation with cancer related death. Results: At the end of the follow-up (average 75 months), 300/537 (55.9%) pts were cured, 100/537 (18.6%) pts showed biochemical disease, 88/537 (16.4%) pts showed metastatic disease and 49/537 (9.1 %) pts died for the disease. The factors significantly correlated with the cancer related death to the univariate analysis were the male gender, dimension of the primary tumor> 4 cm, the presence of lymph node metastasis to histology (N1) and/or distant metastasis (M1) at the time of diagnosis, multifocality, minimal extrathyroidal extension (mETE), initial staging, pre-operative CT values> 500 pg/ml and post-operative> 20 pg/ml. At multivariate analysis, statistical significance persisted only for pre- and post-operative CT and for the staging. Conclusions: 1) In our study we observed a significant improvement in the outcome and survival in the medium-long term of sporadic CMT patients, compared to the previous studies. 2) A more advanced staging at the time of diagnosis has been confirmed as a negative prognostic factor and it is evident that an early diagnosis is an essential requirement for improving cancer related death. 3) This is the first study that showed, in a large monocentric series of sporadic MTCs, as pre-operative CT represents a prognostic factor associated with cancer related death, as well as the value of post-operative CT.